On the Boundary of Life and Society: Biologism in Attempts at Regulative Intervention into Human Nature and Human Society - Janko, Jan (Lidé města, 2000)
In this century science has been accompanied by pseudo-scientific ideas, hypotheses, theories and applications. If the term "pseudoscience" was used, it was largely an emotional label: in fact, these signs were to a large extent based on older scientific ideas, belonging to the "treasury" of the world science and entirely in keeping with the contemporary notions in relevant scientific disciplines and in the community of their bearers. This study focuses on the views, theories and practical approaches which were developed at the boundary of sciences about life and social sciences and which influenced their further development in the intellectual history of the Czech Lands. lt is a complex set of doctrines and disciplines which were alternately described as eugenics, eubiotics, racial hygiene, social health and in many respects they were closely connected with the developing physical, cultural and social anthropology. They can be placed into a number of scientific disciplines about life or medicine, but they are also closely connected with technocratic tendencies which appeared in this country with a varying degree of successfulness and possibly also with social engineering. The time framework of the study is limited to the beginning of the 20th century and it ends in its middle; however, in some cases it crosses both bounds. In terms of space, the focus is reduced to the Czech Lands. However, it is necessary to highlight some vital contexts relating to the development abroad which, as one can expect, played an inspiring role in many respects. Relationships to the development of similar disciplines in neighbouring Germany were of special importance. One cannot erroneously believe that the development of scientific cognition and general education in the Czech Lands was able to avoid some contemporary illusions. Biologism - in the form it was described in a brief reflection of eugenics, eubiotics, social hygiene or biosociology - was among the disciplines which continued to develop in parallel with a more radical development and orientation in Germany, Great Britain and the USA. These disciplines often supplied required pseudo-arguments for racist attitudes in society, reacting to the relevant social order. Nevertheless, the hateful anti-Slov focus of the German racial hygiene constituted the main barrier, due to which the Czech eugenics did not set out on the same path as the German racial hygiene. A special place was assumed by anthropology, especially by its socially orientated part. Although we have highlighted here some phenomena, it will be still better to devote a case study to its development. This is why the author excuses himself for just a brief outline of the problem.